2019
DOI: 10.3389/fpsyg.2019.01740
|View full text |Cite|
|
Sign up to set email alerts
|

Sources of Male and Female Students’ Belonging Uncertainty in the Computer Sciences

Abstract: Belonging uncertainty, defined as the general concern about the quality of one’s social relationships in an academic setting, has been found to be an important determinant of academic achievement, and persistence. However, to date, only little research investigated the sources of belonging uncertainty. To address this research gap, we examined three potential sources of belonging uncertainty in a sample of undergraduate computer science students in Germany ( N = 449) and focused on (a) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 74 publications
(115 reference statements)
2
25
1
Order By: Relevance
“…The higher their perceived potential in comparison to their peers, the less they felt they belonged to their study program. These results stand in stark contrast to the typical findings for female students in STEM domains, where belonging uncertainty is also caused by a perceived academic mismatchalbeit in the form of worries about academic underachievement and inferiority (Höhne & Zander, 2019;Banchefsky et al, 2019). Moreover, researchers suggested that students who belong to minority groups facing a negative ability-related stereotype can be particularly sensitive to the quality of their social bonds in challenging and achievement-oriented environments.…”
Section: Theoretical Backgroundcontrasting
confidence: 66%
See 2 more Smart Citations
“…The higher their perceived potential in comparison to their peers, the less they felt they belonged to their study program. These results stand in stark contrast to the typical findings for female students in STEM domains, where belonging uncertainty is also caused by a perceived academic mismatchalbeit in the form of worries about academic underachievement and inferiority (Höhne & Zander, 2019;Banchefsky et al, 2019). Moreover, researchers suggested that students who belong to minority groups facing a negative ability-related stereotype can be particularly sensitive to the quality of their social bonds in challenging and achievement-oriented environments.…”
Section: Theoretical Backgroundcontrasting
confidence: 66%
“…In university contexts, peer friendships have been shown to emerge out of collaborative academic exchanges (Zander et al, 2018). Furthermore, research has shown that students who feel rejected or excluded by their peers report lower academic self-competence, academic self-concepts, achievement motivation, and belonging (Höhne & Zander, 2019;Walton & Cohen, 2007;Wesselmann et al, 2019), ultimately resulting in lower achievement (Buhs, 2005;Flook et al, 2005;Gopalan & Brady, 2020;Walton & Brady, 2020). Hence, we argue that sensing that one is not part of existing private off-campus or collaborative exchanges to tackle academic challenges can also hold students back from seeking adaptive help from their fellow students in academic settings.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmader and Sedikides (2018) recently argued that sense of “fit” with an environment is multifaceted and dimensions other than social fit also influence an individual’s decision to pursue a domain (see also Höhne and Zander, 2019). They also theorize that evaluations of social belonging are relevant only when social interactions are expected.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty of belonging was found to depend on how participants assessed their own abilities in comparison to that of other students. Additionally, female students' perceived exclusion, both on affective and academic levels, and self-efficacy in the field were further predictors of uncertainty of belonging in the field (Höhne and Zander, 2019). At the college level, it was shown that stereotype threat can hinder women in science from forming social connections to other students, even more so when having lower belonging (Martiny and Nikitin, 2019).…”
Section: Negative Consequences Of Stereotype Threat For Women and Girmentioning
confidence: 96%